Novel palladium (II) complexes with tetradentate thiosemicarbazones. Synthesis, characterization, in vitro cytotoxicity and xanthine oxidase inhibition - Özerkan, Dilşad; Ertik, Onur; Kaya, Büşra; Kuruca, Serap Erdem; Yanardağ, Refiye; Ülküseven, Bahri (Springer Science and Business Media LLC, 2019)
In vitro cytotoxicity and xanthine oxidase inhibition capabilities were investigated for five palladium (II) chelate complexes. The palladium complexes were synthesized by starting from S-alkyl-thiosemicarbazones where the alkyl component is methyl, ethyl, propyl or butyl. The solid complexes are characterized by elemental analysis and spectroscopic techniques (UV-visible, IR and 1H NMR). In order to be able to verify the N2O2-type thiosemicarbazidato ligand (L2-) structure in the square planar geometry, complex 1 has been studied as a representative by using single crystal X-ray crystallography. The in vitro cytotoxic activity measurements were carried out in HepG2 and Hep3B hepatocellular carcinomas, HCT116 colorectal carcinoma, and 3 T3 mouse fibroblast cell lines. The palladium complexes exhibited notable cytotoxic activities in all cell lines at lower μM concentrations compared to the standard chemicals, cisplatin and allopurinol. IC50 values were determined between 0.42 ± 0.01 and 12.01 ± 0.37 μg/ml in examining the antixanthine oxidase abilities of the complexes. Two complexes with S-methyl group exhibited a high inhibition activity on the xanthine oxidase. The results indicated that these complexes could be used as active pharmaceutical ingredients.
Keywords: Thiosemicarbazones; Xanthine Oxidase; Cell Survival; Cytotoxicity; Antineoplastic Agents; T3 Cells; Thiosemicarbazone; Mice; Coordination Complexes; Cell Line, Tumor; Animals; Humans; Xanthine oxidase; Palladium; X-ray analysis